Impact of the COVID-19 Pandemic on the Realization of Organ Donation from Donors Diagnosed with Brain Death: A Narrative Review - Martino, Bruna Verri de; Meneses de Oliveira, Francisco Tomaz (Brazilian Journal of Transplantation, 2026)
The COVID-19 pandemic significantly affected healthcare systems and potentially interfered with different stages of the organ donation and transplantation process. This study aimed to evaluate the impact of the pandemic on the realization of organ donation from donors diagnosed with brain death. A narrative literature review was conducted using the PubMed database, covering studies published from 2019 to 2024, with the descriptors “brain death,” “organ donation,” and “COVID-19.” A total of 39 articles were identified, and after applying the eligibility criteria, seven studies were included in the final analysis. Overall, the studies demonstrated a reduction in organ donation rates, an increase in the time required to complete the donation process, and structural limitations related to healthcare system overload during the pandemic.